2018
DOI: 10.3389/fimmu.2018.02133
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylatoxin Receptors C3aR and C5aR1 Are Important Factors That Influence the Impact of Ethanol on the Adipose Secretome

Abstract: Background and aims: Chronic ethanol exposure results in inflammation in adipose tissue; this response is associated with activation of complement as well as the development of alcohol-related liver disease (ALD). Adipose communicates with other organs, including liver, via the release of soluble mediators, such as adipokines and cytokines, characterized as the “adipose secretome.” Here we investigated the role of the anaphaylatoxin receptors C3aR and C5aR1 in the development of adipose tissue inflammation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…59 Ethanol also modifies the adipokine cargo of EVs released by adipocytes. 60 These ethanol-induced changes in the metabolic and immune function of adipose tissue all contribute to inflammation and injury in the liver.…”
Section: Systemic Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…59 Ethanol also modifies the adipokine cargo of EVs released by adipocytes. 60 These ethanol-induced changes in the metabolic and immune function of adipose tissue all contribute to inflammation and injury in the liver.…”
Section: Systemic Effectsmentioning
confidence: 99%
“…80,81 Further, it is clear that both the anaphylatoxin receptors, complement C3a receptor 1 (C3AR1) and complement C5a receptor 1 (C5AR1), are important for ethanolinduced complement activation to progress to liver inflammation and injury. 60 As with many innate immune functions, while complement activation is pro-inflammatory, it is also required for resolution of injury. For example, complement activation via the alternative pathway is critical to the removal of injured and dying hepatocytes in models of both fibrosis and early ASH.…”
Section: Complementmentioning
confidence: 99%
See 1 more Smart Citation
“…31 This increase of lymphatic density in murine livers during disease was independent of disease etiology (MDR2-/-, Lieber-DeCarli diet and high-fat, lowcholesterol diet) ( Figure 2E and F). 33 Using the HFHC diet model, we found that after 17-24 weeks on the diet, the mice developed steatosis and inflammation, increased aspartate aminotransferase (AST) and alanine aminotransferase (ALT), and increased total cholesterol, high-density lipoprotein, and LDL ( Figure 3A-D). As our model of NASH demonstrates high liver LDL levels, these findings are also consistent with increased LDL exposure causing lymphatic-specific gene downregulation ( Figure 2D).…”
Section: Lymphatic Vasculature Increases In the Liver During The Progmentioning
confidence: 99%
“…Moreover, C3b contributes to the configuration of the C5 convertases that cleave C5, leading to the production of the anaphylatoxin C5a that attracts and activates inflammatory leukocytes, and C5b (Fromell et al, 2020). C5a directly reciprocates with its C5aR on endothelial cells (McCullough et al, 2018), and produces intense changes of the physiologically thrombo-resistant endothelium, such as upregulation of tissue factor and profound decrease of thrombo-modulin, leading to platelet aggregation and adhesion (Gasque et al,1997). As for C5b, it instigates the terminal events of complement activation, resulting in the formation of the membrane-attack complex (MAC or C5b-9 complex), which implants itself into cell Angiotensin-converting enzyme (ACE2) plays a crucial role in the initiation of COVID-19 infection by attaching to the endothelial cells and hence having the domino effect on the infection and defense processes including the complement system.…”
Section: Pathophysiologymentioning
confidence: 99%